Komunikasi Orang Tua Dan Anak Dalam Mencegah Kecanduan Gadget - Siti Maghfirah Fitri (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
The growth of information technology provides various influences in human life, both positive and negative influences. The negative influence of technological developments will cause problems in human life. Among these negative impacts is gadget addiction for children. Parents must play an active role in limiting and protecting children from addiction. One way that parents can do is through a communication approach to children. This study aims to find out how communication between parents and children prevents gadget addiction. The research method uses a qualitative approach with a phenomenological study with research subjects being informants who have children aged 12-15 years. The theory in this research is the Dialogue theory from Martin Burber. The results of this study are that of the three families studied using dialogue as a form of communication within the family to prevent gadget addiction for children. these parents consider dialogue to be more effective than other forms of communication. The obstacles that occur in children are that at the beginning of the dialogue it is not easy to give understanding to children to limit gadgets, and children tend to be silent when having dialogue.